Why Foundation Play an Important Role in Environmental Education: A qualitative analysis at the Adiwiyata School - Adhy Setia Putera; Samsul Maarif; Desvian Bandarsyah; Ihsana El Khuluqo; Moh. Suryadi Syarif; Putri Wulandari (AT-TA'LIM, 2025)
Environmental education faces increasing challenges in sustaining its implementation beyond formal program requirements, particularly in school-based initiatives such as the Adiwiyata program. This study aims to examine the role of school foundation in supporting the implementation of the Adiwiyata program and its influence on students’ environmental awareness in a private junior high school in Tangerang City. A qualitative evaluative approach was employed, with data collected through semi-structured interviews, field observations, and document analysis. The findings reveal that school foundations play a critical role in providing strategic leadership, policy direction, and resource support for environmental education initiatives. However, the effectiveness of these efforts depends on active collaboration among school stakeholders. The study underscores the importance of institutional synergy between foundations and schools to ensure the sustainability of environmental education programs. These findings contribute to the development of best practices for fostering long-term environmental awareness and pro-environmental behavior among student.